2015
DOI: 10.1039/c4ra17014h
|View full text |Cite
|
Sign up to set email alerts
|

Atomic layer-by-layer construction of Pd on nanoporous gold via underpotential deposition and displacement reaction

Abstract: Ultrathin Pd films with one to five atomic layers were decorated on nanoporous gold by underpotential deposition and galvanic displacement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…A powerful strategy that avoids those experimental requirements involves the use of both UPD and galvanic replacement. In the first step, a sacrificial layer of atoms (typically Cu) is deposited onto the surface of electrode‐supported nanocrystals through UPD—the electrodeposition of a partial or complete monolayer of metal atoms onto the surface of nanocrystals maintained at a more positive potential relative to its thermodynamic potential . Afterward, by introducing metal ions of a higher redox potential (e.g., Pt 2+ ), the Cu‐layer (for example) will be oxidized and dissolved while Pt atoms are concomitantly deposited on the surface of the seed, see Figure for an individual Au–Pd nanocrystal encapsulated with a Pt monolayer shell .…”
Section: Other Synthesis Methods For Surface Atomic Replicationmentioning
confidence: 99%
“…A powerful strategy that avoids those experimental requirements involves the use of both UPD and galvanic replacement. In the first step, a sacrificial layer of atoms (typically Cu) is deposited onto the surface of electrode‐supported nanocrystals through UPD—the electrodeposition of a partial or complete monolayer of metal atoms onto the surface of nanocrystals maintained at a more positive potential relative to its thermodynamic potential . Afterward, by introducing metal ions of a higher redox potential (e.g., Pt 2+ ), the Cu‐layer (for example) will be oxidized and dissolved while Pt atoms are concomitantly deposited on the surface of the seed, see Figure for an individual Au–Pd nanocrystal encapsulated with a Pt monolayer shell .…”
Section: Other Synthesis Methods For Surface Atomic Replicationmentioning
confidence: 99%
“…13,14 Providing simple means of surface modification, underpotential deposition (UPD) has also been harnessed for the formation of self-assembled monolayers, [15][16][17][18][19] and the intrinsic limitation to one or two atomic layers makes the UPD process attractive for processing on the nanoscale as exemplified by the growth of layers exploiting surface limited redox replacement (SLRR), [20][21][22] the formation of nanostructures, 23,24 the tailoring of electrocatalysts, 22,25,26 or the modification of nanoparticles. 27,28 Among the numerous UPD systems, 1 Cu on metals such as Au, Ag, Pt, and Pd has been a focus of studies [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] with new aspects in regard to the intricate relationship between structures and deposition conditions continuing to be uncovered.…”
Section: Introductionmentioning
confidence: 99%
“…[128] The same technique was used for Pt deposition on bulk np-Au. [130][131][132] Displacement reactions of Cu with Au and Pd/Pt, respectively, have also been exploited to decorate np-Cu with Au or Pt metals to generate inexpensive, core-shell nanostructures. [130][131][132] Displacement reactions of Cu with Au and Pd/Pt, respectively, have also been exploited to decorate np-Cu with Au or Pt metals to generate inexpensive, core-shell nanostructures.…”
Section: Film Deposition On Np Ligamentsmentioning
confidence: 99%
“…These materials also retained a significant amount of EASA, where the EASA loss of NPG-Pt-Au was 45% compared to a 75% loss for NPG-Pt. [132] More recent work specifically investigated the electocatalytic activity for oxygen reduction, and revealed that Pd coated np-Au shows a higher oxygen reduction activity than np-Au or a commercial Pt/C catalyst. [196] These samples exhibited activity for methanol oxidation, while bare NPG showed none (Figure 17b).…”
Section: Composite Catalystsmentioning
confidence: 99%